2013
DOI: 10.1590/brag.2013.054
|View full text |Cite
|
Sign up to set email alerts
|

Interação genótipo x ambiente em genótipos de cafeeiro Mundo Novo por modelos não lineares e multiplicativos

Abstract: ResumoEste trabalho teve por objetivo avaliar a adaptabilidade e estabilidade fenotípica da produtividade de genótipos do grupo Mundo Novo pelos métodos TOLER e AMMI de maneira a compará-los e a selecionar aqueles que apresentassem alta adaptabilidade produtiva nas regiões produtoras de café do estado de Minas Gerais. Foram instalados e conduzidos experimentos em Três Pontas, Campos Altos e Capelinha, em delineamento de blocos casualizados, com quatro repetições e seis plantas por parcela. Os tratamentos foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(18 reference statements)
0
3
0
1
Order By: Relevance
“…For the Vegetative Vigor (VV), it can be observed that there was no significant difference between the progenies (Table 2), which presented the same note as the controls, recognized by the high vigor (ANDRADE et al, 2013;SILVA et al 2016). Coffee plants with high VV present lesser impoverishment, higher yield and consequently greater tolerance to pests and diseases.…”
Section: Resultsmentioning
confidence: 71%
“…For the Vegetative Vigor (VV), it can be observed that there was no significant difference between the progenies (Table 2), which presented the same note as the controls, recognized by the high vigor (ANDRADE et al, 2013;SILVA et al 2016). Coffee plants with high VV present lesser impoverishment, higher yield and consequently greater tolerance to pests and diseases.…”
Section: Resultsmentioning
confidence: 71%
“…Even though it is not a traditional crop in the region, farmers have been looking for an alternative source of income in coffee cultivation, with the adoption of management practices without any technological reference and with an option for cultivars, made on a subjective basis, since adaptability and the stability of the current 135 Brazilian registered arabica coffee cultivars were evaluated only in the main producing regions of the country (A. M. Carvalho et al, 2016). However, the recommendation of cultivars for Vale do Ribeira Paulista depends on the knowledge of the interaction among genotypes, represented by the cultivars, and this specific cultivation environment (Andrade et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…plantations in Brazil . Possessing high potential, vegetative vigor, and beverage quality, these cultivars have shown wide adaptability and phenotypic stability in different coffee regions of the country (ANDRADE et al., 2013;BOTELHO et al, 2010a). Nevertheless, they are also susceptible to coffee leaf rust caused by the fungus Hemileia vastatrix Berk.…”
Section: Introductionmentioning
confidence: 99%